Fatty Acid Profiles and Their Association With Autoimmunity, Insulin Sensitivity and β Cell Function in Latent Autoimmune Diabetes in Adults - Tian, Huiqin; Wang, Shiqi; Deng, Yating; Xing, Yanke; Zhao, Lin; Zhang, Xia; Zhang, Ping; Liu, Nan; Su, Benli (Frontiers in Endocrinology, 2022)
Background The pathogenesis of the progressive loss of beta cell function latent autoimmune diabetes in adults (LADA) remains still elusive. We aim to study the fatty acid (FA) profile in LADA. Subjects and methods Data from 116 patients with diabetes and GADA and 249 diabetes controls without GADA selected by Propensity Score Matching were collected. FA was analyzed with liquid chromatography-tandem mass spectrometry analysis. Results Principal factor analysis found component 1 explains 82.6% of total variance contained fatty acids from a mixed of lard oil, seafood, and vegetable diet, followed by diet predominantly from vegetable oil, a diet of high fat diet, and a diet of seafood diet. The FA heatmap looked clearly different among the three groups with more similar type 1 (t1dm) and LADA fatty acid profile. n-3 α-linolenic acid (ALA), n-3 long chain polyunsaturated fatty acid (n-3 LC-PUFA), such as Eicosapentaenoic Acid and Docosapentaenoic Acid, n-3/n-6 ratio and triene/tetraene ratio were higher in patients with type 2 diabetes (t2dm) compared with LADA and t1dm. Saturated FAs were lower in t2dm than t1dm and LADA. Arachidic acid and n-6 LC-PUFAs were lower in t2dm than in t1dm and LADA. The characteristics of FAs in LADA were in between of classical t1dm and t2dm. Patients were classified into 6 clusters by FA clusters. Only cluster 2, 3, 5 contained enough patients to be analyzed. Cluster 5 showed an insulin deficient phenotype containing more than 60% of patients with t1dm and LADA and only 12.8% of t2dm. Cluster 2 and 3 were similar. β cell function and glycemic control was better in cluster 3 homing 25% of t2dm. Cluster 2 held 28% of t1dm and LADA, in this cluster more than 60% of patients was t2dm. n-3 linolenic acid, n-3 LC-PUFAs, some n-6 LC-PUFAs, n-3/n-6 ratio and triene/tetraene ratio were negatively associated with GADA positivity while n-6 Arachidonic Acid was associated positively with GADA. Similar findings were found for insulin sensitivity and beta cell function. Conclusion PUFA are associated with insulin sensitivity and beta cell function, and like other clinical features, FA profile distributed differently, but could not be used as makers to differentiate LADA from t1dm and t2dm. Ethics and Dissemination This study has been approved by the Ethical Review Committee of Second Hospital of Dalian Medical University (approval number: 2021–005). Clinical Trial Registration none